Kolaborasi Sosial Mahasiswa dan UMKM : Berbagi Roti Coklat sebagai Wujud Kepedulian Sosial di Panti Asuhan - Nurul Hidayat; Alifah Syaputri; Putri Salsabila Zahra. M; Satri Lapu’; Kristina Sari; Ridwan Ridwan (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2025)
Community Service Activities are a real form of students' social concern for the surrounding environment. Five students of the Management Study Program at Borneo Tarakan University carried out community service in collaboration with local MSME actors through an activity entitled "Sharing Chocolate Bread as a Form of Social Concern". This activity was held on Sunday, May 4, 2025 at 11.00–12.00 WITA at the Hidayah Nurul Yaqin Orphanage, Jl. Sesanip, Karang Anyar, Tarakan, North Kalimantan. The activities included welcoming, praying together, introductions, distributing chocolate bread produced by MSMEs, and documentation. The children of the orphanage welcomed enthusiastically, a warm and pleasant atmosphere was created, and positive interactions were established between students, MSMEs, and the children of the orphanage. This activity brought happiness to the children, became a means of social learning for students, and promoted products for MSMEs. This collaboration shows that synergy between academics and business actors can provide sustainable social contributions.